If it's not what You are looking for type in the equation solver your own equation and let us solve it.
24+6x=6(-5x-8)
We move all terms to the left:
24+6x-(6(-5x-8))=0
We calculate terms in parentheses: -(6(-5x-8)), so:We get rid of parentheses
6(-5x-8)
We multiply parentheses
-30x-48
Back to the equation:
-(-30x-48)
6x+30x+48+24=0
We add all the numbers together, and all the variables
36x+72=0
We move all terms containing x to the left, all other terms to the right
36x=-72
x=-72/36
x=-2
| -(8x-3)=59 | | 7+0.30x=5+0.20 | | .-(8x-3)=59 | | c/7+17=19 | | c7+17=19 | | -3x+28=11x | | 16=u+11 | | -9(x-3)=0 | | 0.99=0.89+10x | | Y=4x^2+24x+39 | | 3=k+13/7 | | 3/4=388x=3/2 | | 3x²+5x+16=0 | | 5.4x=42.12 | | |6m+5=10| | | 1/2x+1.12=15.57 | | x-70=-35 | | .20(2x-5)=25 | | -8.28+6.8v=-2.28+8.1v+2.32 | | 5x+16=5x-7 | | M/6=m-24/14 | | ⅕(2x-5)=25 | | 3=-12/5k | | 3t^2-14-6t=0 | | -3.02-0.7p=0.1p+3.38 | | √6x+4-6=8 | | 5^(2x+1)=7^(x+3) | | 3x(3-3)=27 | | 21=x-(-5) | | 11+(7x+4)=57 | | 11b^2=-11b-12 | | −3x+1=9+5x |